Proposal and assessment of an efficient test configuration for studying lap splices in reinforced concrete. (15th June 2018) - Vieito, Ismael; Herrador, Manuel F.; Martínez-Abella, Fernando; Varela-Puga, Fernando
Highlights: A flexible test setup to study lap splices in reinforced concrete is proposed. Several tensile configurations found in the literature have been studied. An evaluation matrix was used to determine the most efficient alternative. An experimental work has been carried out to assess the proposed test setup. The test resulted to be affordable, with low scatter and with high sensitivity. Abstract: Connecting reinforcement bars in their longitudinal direction is often needed in reinforced concrete structures. These connections must guarantee a correct stress transmission between bars without excessive cracking or inadmissible slips, and they are commonly executed by overlapping the reinforcement bars in a procedure known as a lap splice. In the absence of a standard or widely recognized test, three or four point bending tests are often used for the experimental study of lap-splices in tension. This test configuration shows inherent limitations, large costs and, usually, significant scatter. In this paper the authors have selected, fine-tuned and evaluated a specific test configuration for studying lap splices in reinforcement bars submitted to tensile forces. The proposed experiment was designed to be flexible and affordable in terms of cost, time consumption and required testing equipment. Consequently, it is possible to carry out multiple reruns of the experiments, minimizing the uncertainty and providing a good starting point for applying statistic methodologies. In contrast to the regular test configurations, the selected setup makes possible to directly obtain the bond-slip curves of the spliced bars. The experimental work carried out to assess the reliability, sensitivity and scatter of the proposed configuration shows promising results.